Electric vehicle route recommender system - Ferreira, João C. (2012)
This paper presents a recommender system responsible for processing information that will help the driver in the daily use of his Electric Vehicle (EV), minimizing the problem of range anxiety through a personalized range prediction and by presenting in real time relevant information about the charging stations that can be reached within the range autonomy. Given the success of recommendation systems on automatic delivery of relevant information in numerous areas of usage, this type of systems can also be applied in the electric mobility scenario, with the objective of maximizing the relevance of the information presented to the driver, which should be the strictly needed data for the driver to make important decisions, filtering out the unnecessary information.